Factors Associated with Poor Sleep among Young People in Mauritius: A Survey-Based Study - Yudisha Devi Ramdhany; Smita Sulackshana Devi Goorah; Jayrani Cheeneebash; Ritwij Niketan Oodun (International Journal of Medical Students, 2022)
Background: Poor sleep quality in young people is a global concern. This study was conducted to explore sleep quality and its contributory factors in young people of Mauritius.